A post-marketing pharmacovigilance study of triazole antifungals: adverse event data mining and analysis based on the FDA adverse event reporting system database - Tian, Yalan; Jin, Min; Ning, Hong (Frontiers in Pharmacology, 2025)
BackgroundTo explore and analyze post-marketing adverse drug event (ADE) signals for voriconazole, posaconazole, and isavuconazole, and to compare the safety differences among the three drugs, aiming to provide insights for rational clinical use.MethodsUsing the Open Vigil 2.1 online tool, extract adverse drug event (ADE) report data for voriconazole, posaconazole, and isavuconazole from the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) database from the time the drugs were marketed up to the third quarter of 2023. Employ the Reporting Odds Ratio (ROR) and Proportional Reporting Ratio (PRR) methods for data mining. Filter out ADE signals detected by both the ROR and PRR methods, and categorize these ADE signals by System Organ Class (SOC) according to the Medical Dictionary for Regulatory Activities (MedDRA 26.0).ResultsA total of 8,898 ADE reports with voriconazole as the primary suspect drug were retrieved, 1,948 for posaconazole, and 944 for isavuconazole. From the basic analysis of the adverse event reports, male patients (50.31%) outnumber female patients (32.11%). In terms of age, the majority of patients are over 45 years old (52.72%). The reports primarily come from the United States, Japan, France, China, and other countries. A total of 607 ADE signals were identified, with 402 for voriconazole, 159 for posaconazole, and 46 for isavuconazole. Voriconazole ADEs primarily involved the following SOCs: Investigations (9.45%), Eye Disorders (8.46%), and Nervous System Disorders (7.21%); Posaconazole ADEs primarily involved the following SOCs: Investigations (13.84%), General Disorders and Administration Site Conditions (11.95%), and Nervous System Disorders (6.29%); Isavuconazole ADEs primarily involved the following SOCs: General Disorders and Administration Site Conditions (15.22%), Hepatobiliary Disorders (10.87%), and Blood and Lymphatic System Disorders (10.87%).ConclusionVoriconazole, posaconazole, and isavuconazole all potentially pose safety risks related to hepatobiliary disorders and cardiac disorders. Additionally, voriconazole carries a higher safety risk for eye disorders and nervous system disorders. Newly discovered ADE signals not mentioned in the drug package inserts include voriconazole-induced rhabdomyolysis, posaconazole-induced peripheral neuropathy, and isavuconazole-induced visual impairment and mental confusion. These findings are significant for guiding rational clinical use of these medications.